The story of Wamba : Julian of Toledo's Historia Wambae regis - Julianus, Saint, Bishop of Toledo, -690 (Catholic University of America Press, 2005)
"In 673, the recently elected King Wamba of Spain was confronted with a separatist rebellion in Visigothic Gaul and other territories in the northeast of his realm. After recapturing Barcelona and Gerona, the ruler crossed the Pyrenees at the head of his armies and, taking one fortress after another, followed the retreating rebel forces to the final bastion of Nimes. From there Wamba led the rebels back to Toledo as captives in a triumphal procession. Soon thereafter, Julian, a young priest at the court of Toledo, wrote his Historia Wambae regis, an account of Wamba's accession to the throne and his victory in the first campaign under his command. Julian's work is one of few political narratives of the early middle ages.